Aspects of the Grammar of Eastern Khanty - Filchenko (Фильченко), Andrey (Андрей) (Tomsk State Pedagogical University Press, 2007)
A reference grammar of the endangered indigenous dialects of Vasyugan and Alexandrovo Eastern Khanty of the Uralic language family is the study based on the corpus of natural narrative discourse, and is set in a general cognitive -functional paradigm. The description addresses the main patterns of the Eastern Khanty language system and offers typological contextualization of the reviewed language data. The description covers the issues in phonology (backness vowel harmony, consonant-vowel harmony), word-classes, morphology (derivation and inflection), syntax and semantics of simple and complex clauses (typical SOV patterns with occasional non-canonical argument ergative marking against the general background of Nom-Acc system and robust use of non-finite and finite constructions as relative, adverbial and complement clauses).
Keywords: Eastern Khanty; language; phonology; word-classes; morphology